2012
DOI: 10.1159/000339154
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Adiponectin Levels in Korean Children with a Family History of Type 2 Diabetes Mellitus

Abstract: Background/Aims: The current worldwide increases of type 2 diabetes mellitus (T2DM) in children coincide with increases in the prevalence of obesity. We investigated the insulin resistance and adiponectin levels of children and adolescents with a family history of T2DM (FHD). Methods: Our sample included 131 children and adolescents aged 8–15 years. Fasting plasma glucose, lipids, fasting insulin, adiponectin levels and HOMA-IR were analyzed according to FHD and obesity. Oral glucose tolerance tests were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 72 publications
0
4
1
Order By: Relevance
“…However, this trend was not observed in children whose mothers or other relatives had a history of DM. This disagrees with Joung et al [25], who reported that adiponectin concentrations were independently related to a family history of diabetes. This may be explained by the fact that children of diabetic parents often exhibit signs of excess body lipid as early as childhood, and the development of insulin resistance syndrome in childhood can accelerate into young adulthood [26].…”
Section: Discussioncontrasting
confidence: 83%
“…However, this trend was not observed in children whose mothers or other relatives had a history of DM. This disagrees with Joung et al [25], who reported that adiponectin concentrations were independently related to a family history of diabetes. This may be explained by the fact that children of diabetic parents often exhibit signs of excess body lipid as early as childhood, and the development of insulin resistance syndrome in childhood can accelerate into young adulthood [26].…”
Section: Discussioncontrasting
confidence: 83%
“…A family history of T2D was shown to be another important factor for the onset of T2D in obese Japanese children. Oh et al 24 showed that obese Korean children and adolescents with a family history of T2D were more insulin resistant and had lower serum adiponectin levels, compared with an obese group without a family history of T2D. Another study has also shown that a family history of T2D in white youths was associated with reduced insulin sensitivity 25 …”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin is produced by adipocytes, and then secreted in the circulation of human healthy individuals at relatively high levels, which fluctuates between 5 and 30 μg/ml (19). However, the levels of this adipokine is reduced in patients with insulin resistance (20), type II diabetes mellitus (T2DM) (21, 22), obesity (23), cardiovascular disease (24), metabolic syndrome (25), and NAFLD (26-29). …”
Section: Introductionmentioning
confidence: 99%